Collaborative writing. (21st December 2018) - Storch, Neomy
Abstract : Writing has generally been perceived as a solitary activity, completed by the writer working alone. Yet, over the years we have witnessed a growing interest among researchers and educators inCollaborative Writing, an activity that can be simply defined as the involvement of two or more writers in the production of a single text. This interest has been driven by two main factors. The first factor is the nature of workplace writing. Studies (e.g. Ede & Lunsford1990 ; Mirel & Spilka2002 ) have shown that in a number of workplaces, writing is often completed in teams rather than individually. The second factor is the advent of Web 2.0 applications such as blogs, wikis, and Google Docs, which have transformed literacy practices, making the creation and sharing of texts easier and more readily acceptable (Hyland2016 ; Vandergriff2016 ). In the field of second language (L2) learning, interest in collaborative writing was also spurred by early research conducted by Swain and her colleagues (e.g. Swain & Lapkin1995 ; Swain1998 ; see also timeline for additional references) showing the language learning opportunities of communicative tasks which involve joint written output (e.g. Dictogloss).